2017
DOI: 10.1371/journal.pone.0179563
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of community-associated methicillin-resistant Staphylococcus aureus clones in a maternity hospital

Abstract: BackgroundMethicillin- resistant Staphylococcus aureus (MRSA) is a major pathogen causing healthcare- and community- acquired infections. The purpose of this study was to characterize MRSA isolated at the Maternity Hospital between 2006 and 2011 for their genetic relatedness.Materials and methodsThe MRSA isolates were investigated using a combination of antibiogram, Staphylococcal chromosome cassette mec (SCCmec) and spa typing to determine their relatedness to MRSA isolated in other Kuwait hospitals. The isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
5
16
0
1
Order By: Relevance
“…In Kuwait, CC239-MRSA-III accounted for more than 50% of typed MRSA isolates collected in a period from 1992 to 2010 (Boswihi et al, 2016 ). Currently, it is still present although it appears to be replaced by community-acquired MRSA strains (Udo and Al-Sweih, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Kuwait, CC239-MRSA-III accounted for more than 50% of typed MRSA isolates collected in a period from 1992 to 2010 (Boswihi et al, 2016 ). Currently, it is still present although it appears to be replaced by community-acquired MRSA strains (Udo and Al-Sweih, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported the local predominance of this clone in many countries including European countries [143,144], the Middle East, Asia, and South America [145]. Another epidemic clone, MRSA-ST22, has been predominately identified in recent years throughout the Middle East [44,45,[146][147][148][149][150][151][152][153][154], Europe [155][156][157][158][159][160], and Asia [161][162][163]. For North Africa, the lower number of studies on MRSA means that MRSA lineages remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of the total MRSA strains, MRSA-ST80 prevalence was 3% (3/102) in Turkey [38], 4% (3/79) in Oman [39], 10% (2/21) in Egypt [40], 19% (10/52) in United Arab Emirates [41], and 31% (37/121) in Palestine [42]. In Kuwait, the reported proportions of MRSA-ST80 among MRSA strains were 38.4% (10/26) [45]. In Jordan, MRSA-ST80 strains were detected in 34.1% (14/41) of all MRSA strains recovered from infections from 2009 to 2010 [46].…”
Section: Middle Eastmentioning
confidence: 99%
“…The dynamics of the prevalence of S. aureus clones, including MRSA and MSSA strains, have been recently investigated 6 . As a consequence, the changes in the epidemiological overview have been observed worldwide, revealing the emergence of new clones replacing the previously established ones 7,8 . As monitoring resistance and virulence profiles is important to establish control strategies, here we aimed to analyze and compare the antimicrobial resistance patterns, virulence profiles, and molecular epidemiology of S. aureus strains isolated from a public hospital located in south-eastern Brazil.…”
Section: Introductionmentioning
confidence: 99%